Holography at Work for Nuclear and Hadron Physics - Youngman Kim; Deokhyun Yi (Advances in High Energy Physics)
The purpose of this review is to provide basic ingredients of holographic QCD to nonexperts in string theory and to summarize its interesting achievements in nuclear and hadron physics. We focus on results from a less stringy bottom-up approach and review a stringy top-down model with some calculational details.